2016
DOI: 10.1177/1354816616669008
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from tourist activities in South Tyrol

Abstract: Tourism is a non-negligible source of greenhouse gas (GHG) emissions. Using South Tyrol (ST) – a small region with a tourism-intensive economy situated in the North of Italy – as a case study, this article discusses a multiregional input–output (MRIO) framework for calculating the direct and indirect emissions embodied in tourist consumption of goods and services at a subnational level. Compared to more standard single-region implementations of the input–output approach, MRIO analysis offers a more accurate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The relationship between environmental conditions and tourism activity is widely studied in the literature. This connection is documented by several empirical studies considering different environmental quality measures and tourism development indicators (Becken and Hay, 2007; Black, 2004; Bojanic and Warnick, 2019; Cai, 2016; Giannoni and Maupertuis, 2007; Gössling et al, 2002; Høyer, 2000; Katircioglu et al, 2018a; Scott, 2011; Scott et al, 2012, 2019; Tang and Ge, 2018; Tovar and Lockwood, 2008; Wang and Wang, 2018). From a theoretical point of view, Gupta and Dutta (2016) develop the more recent dynamic model of a developing economy where environmental quality and capital stock accumulate over time and where tourism development raises the level of capital stock and national income but lowers the quality of the environment, leading to a relative contraction of the labor-intensive tourism sector.…”
Section: Related Literaturementioning
confidence: 83%
“…The relationship between environmental conditions and tourism activity is widely studied in the literature. This connection is documented by several empirical studies considering different environmental quality measures and tourism development indicators (Becken and Hay, 2007; Black, 2004; Bojanic and Warnick, 2019; Cai, 2016; Giannoni and Maupertuis, 2007; Gössling et al, 2002; Høyer, 2000; Katircioglu et al, 2018a; Scott, 2011; Scott et al, 2012, 2019; Tang and Ge, 2018; Tovar and Lockwood, 2008; Wang and Wang, 2018). From a theoretical point of view, Gupta and Dutta (2016) develop the more recent dynamic model of a developing economy where environmental quality and capital stock accumulate over time and where tourism development raises the level of capital stock and national income but lowers the quality of the environment, leading to a relative contraction of the labor-intensive tourism sector.…”
Section: Related Literaturementioning
confidence: 83%
“…Using a multiregional input-output model, Cai (2016) analyzed the impact of greenhouse gas emissions resulting from tourism activities in South Tyrol, a tourist region in northern Italy. The main results showed that in 2010, the production of goods and services consumed by tourists resulted in emissions of 1092 kt CO2e, which corresponds to average emissions of 38 kg CO2e per night or 0.316 kg per euro spent on tourist products and services.…”
Section: Tourism and Input-outputmentioning
confidence: 99%
“…Existing studies on tourism carbon emissions have yielded fruitful results, and many studies have conducted a series of empirical analyses on carbon emissions from tourism transportation (Becken, 2002;Filimonau and Hogstrom, 2017;Howitt et al, 2010;Simonsen et al, 2019), tourism accommodations (Becken et al, 2001;Filimonau et al, 2011a;Tsai et al, 2014), tourism stakeholders (Bocken and Allwood, 2012;Cadarso et al, 2015), tourism destinations, and the tourism industry (Cai, 2016;Dubois and Ceron, 2006;Sun, 2014;Zha et al, 2019a). To conclude, findings of the above studies vary greatly due to differences in analytical methodologies, sample selection, and research perspective, whereas many studies have confirmed that tourism transportation, accommodations, and catering have proved to be the main sources contributing to the increase in tourism carbon emissions (Go ¨ssling et al, 2015;Higham et al, 2016;Zhang et al, 2016) Tourism often includes transportation, accommodations, catering, sightseeing, and other activities.…”
Section: Literature Reviewmentioning
confidence: 99%